(untitled) (Journal of actual problems of jurisprudence, 2023)
Indirect methods in judicial and investigative practice are an important tool for solving especially dangerous crimes. The complexity of the specific circumstances of the crime is such that it is impossible to obtain direct evidence at the initial stage of the investigation, and sometimes even later. The purpose is to show the procedure for using indirect methods used in identifying evidence in the course of criminal proceedings in the country. The main meaning of this article is to clarify the meaning of indirect actions in the course of criminal proceedings. Explain what mistakes are made when using it and the importance of working with them. In the course of the study, information was collected on criminal proceedings and the Criminal Code of the Republic of Kazakhstan was used. Situational examples are given and it is written which indirect methods can be used. The theoretical base, which includes the analysis of the concept of indirect methods and evidence, the definition of features, the meaning and place of evidence in the criminal process, is necessary for practice, the stages of the proof process are fully covered. The main purpose of this article is to identify the main features of proof by indirect methods, a description of the features and stages of proof. Key words: evidence, indirect method, criminal case, circumstantial evidence, direct evidence, criminal process, criminal proceedings.